2009
DOI: 10.1137/080733371
|View full text |Cite
|
Sign up to set email alerts
|

Linearized Bregman Iterations for Frame-Based Image Deblurring

Abstract: Abstract. Real images usually have sparse approximations under some tight frame systems derived from framelets, an oversampled discrete (window) cosine, or a Fourier transform. In this paper, we propose a method for image deblurring in tight frame domains. It is reduced to finding a sparse solution of a system of linear equations whose coefficient matrix is rectangular. Then, a modified version of the linearized Bregman iteration proposed and analyzed in [10,11,44,51] can be applied. Numerical examples show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
172
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(174 citation statements)
references
References 42 publications
(109 reference statements)
0
172
0
Order By: Relevance
“…The procedure is repeated and it converges to a sparse solution in the framelet domain. The algorithm is efficient and robust to noises as analyzed by [5] and we also have the following convergence results from [5]. See [4,5,6,32] for a more detailed analysis.…”
Section: Methods For Step 2 In Algorithmmentioning
confidence: 77%
See 3 more Smart Citations
“…The procedure is repeated and it converges to a sparse solution in the framelet domain. The algorithm is efficient and robust to noises as analyzed by [5] and we also have the following convergence results from [5]. See [4,5,6,32] for a more detailed analysis.…”
Section: Methods For Step 2 In Algorithmmentioning
confidence: 77%
“…Step 2 is a non-blind image deblurring problem, which has been studied extensively in the literature; see, for instances, [1,22,8,7,18,5]. However, there is one more error source in Step 2 than the traditional non-blind deblurring problem has, that is, the error in the intermediate blur kernel p (k+1) i used for deblurring.…”
Section: Given the Clear Image G (K)mentioning
confidence: 99%
See 2 more Smart Citations
“…As we will show later, the perfect reconstruction property of tight framelet system allows the application of the so-called linearized Bregmen iteration (Osher et al [21]), which has been shown in recent literatures (Cai et al [6,5]) that it is more efficient than classic numerical algorithms (e.g. interior point method) do when solving this particular type of ℓ 1 norm minimization problems.…”
Section: Our Approachmentioning
confidence: 99%